Socio-economic Correlates, Technological Gap and Training Nneeds of the Farmers for Increasing Pineapple Productivity in Meghalaya - Das, J. K.; Sangma, Lima N.; Majumder, D. (International Journal of Bio-resource and Stress Management, 2017)
The study was conducted during 2012–13 to identify the role of different socio-economic variables on yield, income, technological gap and training need confronting the productivity of pineapple in the state of Meghalaya. Study revealed that the variable economic motivation (0.130) have recorded a positive and significant correlation with the variable income, of the respondents. The correlation coefficient between yield (Y2) and all independent variables revealed that education of farmers (0.125), Market orientation (0.095) and cultivation efficiency (0.130) have recorded significant and positive correlation with the yield of the respondents. It is also recorded that variables Family type (-0.105), Management orientation (-0.167) and utilization of mass media (-0.137) are significant but negatively correlated with the yield of pineapple. In the path analysis, it has been found that the variable utilization of mass media has routed highest indirect effect on income as many as 16 exogenous variables. Similarly, it has also identified that both the variables management orientation and education of farmers have routed highest indirect effect on yield as many as 8 exogenous variables. The result of technological gap revealed that the highest gap (60.75%) and the lowest gap (30.50%) was found in the knowledge of ‘sucker’ and in ‘post harvest technology’ respectively among the pineapple growers. The farmers have shown maximum interest (rank-I) for training on ‘improved cultural practices’ (59.66%) and minimum interest (rank-X) on ‘cropping system’ (45.86%) in pineapple cultivation.